Identification of Novel and Conserved miRNAs in Leaves of In vitro Grown Citrus reticulata “Lugan” Plantlets by Solexa Sequencing - Guo, Rongfang; Chen, Xiaodong; Lin, Yuling; Xu, Xuhan; Thu, Min Kyaw; Lai, Zhongxiong (Frontiers in Plant Science, 2016)
MicroRNAs (miRNAs) play essential roles in plant development, but the roles in the in vitro plant development are unknown. Leaves of ponkan plantlets derived from mature embryos at in vitro culture conditions were used to sequence small RNA fraction via Solexa and the miRNAs expression was analyzed. The results showed that there were 3,065,625 unique sequences in ponkan, 0.79% of which were miRNAs. The RNA sequences with lengths of 18–25 nt derived from the library were analyzed, leading to the identification of 224 known miRNAs, of which the most abundant were miR157, miR156, and miR166. 358 novel miRNA candidates were also identified and the number of reads of ponkan novel miRNAs varied from 5 to 168,273. The expression of the most known miRNAs obtained was at low levels, varied from 5 to 4,946,356. To better understand the role of miRNAs during the preservation of ponkan in vitro plantlet, the expression patterns of cre-miR156a/159b/160a/166a/167a/168a/171/398b were validated by quantitative real-time PCR. The results showed that not only the development-associated miRNAs, e.g. cre-miR156/159/166/396, expressed highly at the early preservation period in the in vitro ponkan plantlet leaves, but the stress-related miRNAs, e.g. cre-miR171 and cre-miR398b, were also expressed at high levels at the same time. The expression levels of most tested miRNAs were found decreased after 6 months and the amounts of these miRNAs kept at low levels at the period of the 18th months. After analyzed the expression level of their targets during the reservation of the ponkan in vitro plantlet, development-associated cre-ARF6 and stress-related cre-CSD modules exhibited negative correlation with miR167 and miR398 respectively, indicating an involvement of the miRNAs in the in vitro development of ponkan, and function in the conservation of ponkan germplasm.